Acute graft-versus-host disease following lung transplantation in a patient with a novel TERT mutation. Issue 5 (30th January 2018) - Brestoff, Jonathan R; Vessoni, Alexandre T; Brenner, Kirsten A; Uy, Geoffrey L; DiPersio, John F; Blinder, Morey; Witt, Chad A; Byers, Derek E; Hachem, Ramsey R; Truclock, Elbert P; Early, Dayna S; Anadkat, Milan J; et al.
Abstract : Familial pulmonary fibrosis is associated with loss-of-function mutations in telomerase reverse transcriptase ( TERT ) and short telomeres. Interstitial lung diseases have become the leading indication for lung transplantation in the USA, and recent data indicate that pathogenic mutations in telomerase may cause unfavourable outcomes following lung transplantation. Although a rare occurrence, solid organ transplant recipients who develop acute graft-versus-host disease (GVHD) have very poor survival. This case report describes the detection of a novel mutation in TERT in a patient who had lung transplantation for familial pulmonary fibrosis and died from complications of acute GVHD.